2021
DOI: 10.1002/cssc.202002824
|View full text |Cite
|
Sign up to set email alerts
|

Hypercrosslinked Polymers as a Photocatalytic Platform for Visible‐Light‐Driven CO2Photoreduction Using H2O

Abstract: The design of robust, high‐performance photocatalysts is key for the success of solar fuel production by CO2 conversion. In this study, hypercrosslinked polymer (HCP) photocatalysts have been developed for the selective reduction of CO2 to CO, combining excellent CO2 sorption capacities, good general stabilities, and low production costs. HCPs are active photocatalysts in the visible light range, significantly outperforming the benchmark material, TiO2 P25, using only sacrificial H2O. It is hypothesized that s… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
46
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 51 publications
(48 citation statements)
references
References 43 publications
2
46
0
Order By: Relevance
“…Recently, organic polymer materials including covalent organic frameworks (COFs) [ 8 ] and covalent microporous polymers (CMPs) [ 9 ] have been suggested as promising photocatalysts owing to their irreplaceable advantages including facile structural controllability, high CO 2 adsorption capacity, excellent structural stability, and wide spectral response range. [ 10 –‐ 12 ] Nevertheless, sacrificial reagents, e.g. triethanolamine, triethylamine, and triisopropanolamine, are still necessary so far to reduce CO 2 for most of organic polymer photocatalytic systems.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, organic polymer materials including covalent organic frameworks (COFs) [ 8 ] and covalent microporous polymers (CMPs) [ 9 ] have been suggested as promising photocatalysts owing to their irreplaceable advantages including facile structural controllability, high CO 2 adsorption capacity, excellent structural stability, and wide spectral response range. [ 10 –‐ 12 ] Nevertheless, sacrificial reagents, e.g. triethanolamine, triethylamine, and triisopropanolamine, are still necessary so far to reduce CO 2 for most of organic polymer photocatalytic systems.…”
Section: Introductionmentioning
confidence: 99%
“…20 HCP-based catalysts were employed for a wide array of transformations, ranging from biomass conversion 21,22 to the photocatalytic reduction of CO2. 23,24 High surface areas allow for an abundance of catalytically active sites and hierarchically porous structures are beneficial to the mass transfer of reactants and products. As such, HCPs show excellent ability in catalysis and are ideal candidates for industrial applications in accordance with the principles of green chemistry.…”
Section: Introductionmentioning
confidence: 99%
“…[30] Schukraft et al reported a triazine ring-containing HCPs platform with similar photocatalytic performance toward CO 2 photoreduction to commercial P25 owing to the selective adsorption. [31] Although there are numerous reports of HCPs achieving great progress in the fields of CO 2 capture and storage, their photocatalytic applications for CO 2 conversion are restricted by the low quantum efficiency, relative to semiconductor photocatalysts like TiO 2 , due to the blocked conjugated structure by crosslinked methylene agent. [32,33] To combine the advantages of HCPs and TiO 2 photocatalyst, in the previous work, we proposed an in situ knitting strategy for constructing HCPs on TiO 2 surface using the functionalized graphene (FG) skeleton to provide the open phenyl group for covalent linking with syn-PhPh 3 .…”
Section: Introductionmentioning
confidence: 99%